Crecimiento económico de la Empresa Agro Integral Azogue del cantón Palenque, período 2023. - Murrieta Sánchez, Ginger Angelina (2025)
Economic growth is what every company hopes to achieve in a certain period of time and for it to be maintained in the long term. For this reason, proper management of resources is important, since these will allow us to achieve this purpose through high productivity. The objective of this research is to analyze the economic growth in the company Agro Integral Azogue in the period 2023, through data collection to determine marketing strategies and improve its commercial performance. In the case study, the methodological approach method was used, while its approach was descriptive since the variable was analyzed from different angles. The techniques used were an interview with the company's administrators and a survey with its clients. He results in relation to the strategies applied in the context of customer service indicate that there is a philosophy of hiring staff that empathizes effectively with customers, an aspect that is relevant to economic growth because it means that the company is more likely to obtain customer loyalty and consequently sales increase, which promotes business development to remain competitive in the market in which it operates. The conclusions of the study are that the marketing strategies implemented by the analyzed company are a key success factor to achieve economic growth, so it is recommended to continue updating the technological mechanisms to obtain a greater scope of the same.